Model‐Informed Drug Development and Review for Generic Products: Summary of FDA Public Workshop. Issue 1 (30th March 2018) - Fang, Lanyan; Kim, Myong‐Jin; Li, Zhichuan; Wang, Yaning; DiLiberti, Charles E.; Au, Jessie; Hooker, Andrew; Ducharme, Murray P.; Lionberger, Robert; Zhao, Liang
Abstract : On October 2 nd and 3 rd, 2017, the US Food and Drug Administration (FDA) hosted a public workshop titled "Leveraging Quantitative Methods and Modeling to Modernize Generic Drug Development and Review." 1 This report summarizes Session 2 of the public workshop: "Model Informed Drug Development and Review for Generic Products." The session focused on the application of quantitative methods and modeling in modernizing the generic drug development and review.